Antibody Profiling of COVID-19 Patients in an Urban Low-Incidence Region in Northern Germany - Solbach, Werner; Schiffner, Julia; Backhaus, Insa; Burger, David; Staiger, Ralf; Tiemer, Bettina; Bobrowski, Andreas; Hutchings, Timothy; Mischnik, Alexander (Frontiers in Public Health, 2020)
A vast majority of COVID-19 cases present with mild or moderate symptoms. The study region is in an urban and well-defined environment in a low-incidence region in Northern Germany. In the present study, we explored the dynamics of the antibody response with respect to onset, level and duration in patients with confirmed SARS-CoV-2 infection. Anti-SARS-CoV-2 IgG and IgA were detected by automated enzyme-linked immunosorbent assay - ELISA of SARS-CoV-2 infected patients monitored by Health Protection Authority. This explorative monocentric study shows IgA and IgG antibody profiles from 118 patients with self-reported mild to moderate, or no COVID-19 related symptoms after laboratory-confirmed infection with SARS-CoV-2. We found that 21.7 % and 18.1 % of patients were seronegative for IgA or IgG, respectively. Clinically, most of the seronegative patients showed no to only moderate symptoms. With regard to antibody profiling 82 % of all patients developed sustainable antibodies (IgG) and 78 % (IgA) 3 weeks or later after the infection. Our data indicate that antibody-positivity is a useful indicator of a previous SARS-CoV-2 infection. Negative antibodies do not rule out SARS-CoV-2 infection. Future studies are needed to determine the functionality of the antibodies in terms of neutralization capacity leading to personal protection and prevention ability to transmit the virus as well as to protect after vaccination.